A collagen membrane containing osteogenic protein-1 facilitates bone regeneration in a rat mandibular bone defect. (December 2017) - Ozaki, Manami; Takayama, Tadahiro; Yamamoto, Takanobu; Ozawa, Yasumasa; Nagao, Mayu; Tanabe, Natsuko; Nakajima, Akira; Suzuki, Naoto; Maeno, Masao; Yamano, Seiichi; Sato, Shuichi
Highlights: BCM/OP-1 indicates significantly enhancement on osteogenesis in vivo . OP-1 delivery using a BCM may lead to an improvement in the clinical treatment of bone defects. BCM/OP-1 may provide a safe and effective on bone regeneration. BCM/OP-1 is a great candidate to stimulate bone regeneration. Abstract: Objectives: Osteogenic protein-1 (OP-1) has shown osteoinductive activities and is useful for clinical treatments, including bone regeneration. Regenerative procedures using a bioabsorbable collagen membrane (BCM) are well established in periodontal and implant dentistry. We evaluated the subsequent effects of the BCM in combination with OP-1 on bone regeneration in a rat mandibular circular critical-sized bone defect in vivo . Design: We used 8 rats that received surgery in both sides of the mandible, and created the total 16 defects which were divided into 4 groups: Group 1; no treatment, as a control, Group 2; BCM alone, Group 3; BCM containing low dose 0.5 μg of OP-1 (L-OP-1), and Group 4; BCM containing high dose 2.0 μg of OP-1 (H-OP-1). Newly formed bone was evaluated by micro computed tomography (micro-CT) and histological analyses at 8 weeks postoperatively. In quantitative and qualitative micro-CT analyses of the volume of new bone formation, bone density, and percentage of new bone area was evaluated. Results: BCM with rhOP-1 significantly increased and accelerated bone volume, bone mineral density, and percentage of new bone area compared to control and BCM alone at 8 weeks after surgery; these enhancements in bone regeneration in the OP-1-treated groups were dose-dependent. Conclusions: OP-1 delivered with a BCM may have effective osteoinductive potency and be a good combination for bone regeneration. The use of such a combination device for osteogenesis may result in safer and more predictable bone regenerative outcomes in the future.